Synthesis of Novel S-Glucosides Containing 5-Methylisoxazole Substituted 1,2,4-Triazole - Shujun Chao; Yingling Wang (Journal of Chemistry)
Nine new S-β-D-glucosides containing 4-aryl-5-(5-methylisoxazol-3-yl)-1,2,4-triazol-3-thiols have been synthesized by the direct glycosylation of 4-aryl-5-(5-methylisoxazol-3-yl)-1,2,4-triazol-3-thiols with 2,3,4,6-tetra-O-acetyl-α-D-glucopyranosyl bromide in ethanol in the presence of potassium hydroxide followed by deacetylation using dry ammonia in dry methanol. All the compounds synthesized have been characterized by their elemental analyses and spectral data.